Effect of formulation compositions on niosomal preparations. (June 2013) - Chaw, Cheng Shu; Ah Kim, Kwong Yioung
<x xml:space="preserve">Abstract</x> This study was aimed to investigate the effects of molar ratio of cholesterol to Span 60 and stabilizers (Solutol HS 15 or dicetyl phosphate (DCP)) on the entrapment of methylene blue, a model hydrophilic drug. The niosomes were prepared by the film hydration method and characterized for drug entrapment efficiency (EE), vesicle size, zeta potential and thermal properties of niosomal membrane. It was found that niosomal vesicles possessed median diameter ranging from 0.35 to 1.85 μm. The niosomes that were formulated with lower molar ratios of cholesterol to Span 60 of 0.33 and 0.50 produced significantly higher EE with both stabilizers when compared to cholesterol to Span 60 molar ratios of 1.0 and above (p < 0.05). The EE of niosomes stabilized with DCP was significantly higher (p < 0.05) than those prepared with Solutol HS 15 except at a molar ratio of cholesterol to Span 60 of 0.33. In conclusion, with low molar ratios of cholesterol to Span 60, more drugs could be entrapped within the niosomes regardless of the type of stabilizers. Furthermore, EE and median diameter of niosomes containing DCP were higher than those stabilized with Solutol HS 15.